Rickettsia parkeri colonization in Amblyomma maculatum: the role of superoxide dismutases. Issue 1 (December 2016) - Crispell, Gary; Budachetri, Khemraj; Karim, Shahid
Abstract Background The Gulf Coast tick (Amblyomma maculatum ) is an arthropod vector ofRickettsia parkeri, the causative agent of American boutonneuse fever and an infectious agent of public health significance. In this study, we evaluated the biological significance of the superoxide dismutases (SODs) ofA. maculatum in hematophagy andR. parkeri colonization within the tick host. Methods An RNA interference approach was used to measure the functional roles of tick SODs (Cu/Zn-SOD andMn-SOD ) inR. parkeri colonization of the tick vector. Total microbial load, R. parkeri infection rate, and compensatory mechanisms by tick genes were examined using quantitative polymerase chain reaction (PCR) and quantitative reverse-transcriptase PCR assays. SOD enzymatic activity assays and malondialdehyde (MDA) lipid peroxidation were employed to determine the redox states in the tick tissues. Results Knockdown of theCu/Zn-SOD gene caused the upregulation ofMn-SOD in transcript levels. Single and dual knockdowns of the SOD genes caused an increase in MDA lipid peroxidation while SOD enzymatic activities did not show a significant change.Mn-SOD knockdown resulted in a substantial increase in the microbial load; however, Cu/Zn-SOD transcript depletion prompted an upsurge in the midgut bacterial load, and significantly decreased the bacterial load in salivary gland tissues. Additionally, Cu/Zn-SOD transcript silencing led to significantly fewerR. parkeri DNA copy numbers in both tick tissues (midguts and salivary glands). Conclusions SOD enzymes play an important function in the regulation of bacterial communities associated with tick vectors and also in the defense mechanisms against the damage caused by reactive oxygen species within the tick. Knockdown experiments increased the levels of total oxidative stress in ticks, revealing the interplay between SOD isozymes that results in the transcriptional regulation of tick antioxidants. Moreover, the tick'sCu/Zn-SOD aids in the colonization of R. parkeri in tick tissues providing evidence ofA. maculatum's vectorial success for a spotted fever group rickettsial pathogen.